The Saint and the monster: a reading of Michel Tournier’s - Wimmer, Norma (Lettres Françaises, 2008)
In Michel Tournier’s "Gilles et Jeanne" (1983) the author revisits the history of Joan of Arc through its dark side, the character Gilles de Rais. This paper approaches mathers related to the representation of this character taking into account the process of literary creation.